Annexin A2: Its Molecular Regulation and Cellular Expression in Cancer Development. (23rd January 2014) - Wang, Chi-Yun; Lin, Chiou-Feng
Abstract : Annexin A2 (ANXA2) orchestrates multiple biologic processes and clinical associations, especially in cancer progression. The structure of ANXA2 affects its cellular localization and function. However, posttranslational modification and protease-mediated N-terminal cleavage also play critical roles in regulating ANXA2. ANXA2 expression levels vary among different types of cancers. With some cancers, ANXA2 can be used for the detection and diagnosis of cancer and for monitoring cancer progression. ANXA2 is also required for drug-resistance. This review discusses the feasibility of ANXA2 which is active in cancer development and can be a therapeutic target in cancer management.